The Fulfillment of Psychological Contract and Job Satisfaction in Reducing Procrastination of Employees Working in the Public SectorPublic Sector - Sunarta, Sunarta; Wardana, Wardana; Nuranti, Barida Rakhma (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to examine the factors that influence procrastination among education staff at a university. The research used mono methods: quantitative method, survey strategy, and cross-sectional research design. The data were collected by questionnaires distributed offline and online via Google Forms to 145 education staff at a state university in Yogyakarta. The data were analyzed using the Structural Equation Modeling equation based on Partial Least Square (SEM PLS). The research found that achievement motivation and organizational commitment influence procrastination directly and through the mediation of fulfilling the psychological contract. Meanwhile, job satisfaction does not significantly affect procrastination, nor does it mediate the influence of achievement motivation and organizational commitment on procrastination. The research results were then discussed according to the characteristics of organizations in the public sector in higher education.